LC21 : a digital strategy for the Library of Congress (National Academy Press, 2000)
This report provides strategic advice on the information technology path that the Library of Congress should traverse in the coming decade. It covers how information technology could affect LC's mission and core processes including the acquisition, collection, preservation, and accessibility of digital materials, and the information technology infrastructure.